LEGAL REMEDIES AGAINST TRADITIONAL LAND SALE AND PURCHASE DISPUTES IN POSITIVE LAW STUDY - Gusti Heliana Safitri; Ekawati Ekawati; Sarikun Sarikun; Dina Paramitha Hefni Putri; Khairunnisah Khairunnisah (Faculty of Law, Universitas Pekalongan, 2023)
Land is an economic driving object for humans and the state whose use cannot be separated from politics and law, as well as the function of realizing mutual benefit. Conflict over customary land is a social phenomenon that can be explained through various sociological bases. This sociological foundation helps us understand the root causes, dynamics and implications of conflicts related to customary land ownership and use. Customary land disputes can vary depending on the culture, traditions and value systems of the indigenous peoples concerned. resolving customary land disputes often requires a deep understanding of the culture and values of the community, as well as respect for their rights in the context of national and international law. In this case, what legal measures can be taken in relation to disputes regarding customary land from a positive legal perspective in Indonesia The research method is a type of normative legal research or research using the rules in existing laws and regulations and research carried out by collecting data directly in the field from competent parties related to the object under study, because it is in the form of secondary data such as laws and regulations. literature books . The court decision will regulate the land rights and obligations of each party. disputes over the sale and purchase of customary land can trigger reconsideration of customary regulations or land law in Indonesia. This could mean changes in the practice of buying and selling customary land as a form of implementing agrarian reform with settlement. Settlement of land disputes using the ADR mechanism is carried out based on Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, in conjunction with Law no. 48 of 2009 concerning Judicial Power, and various other legal provisions such as Supreme Court Regulation (PERMA) Number 1 of 2008 concerning Mediation Procedures in Court, which has been replaced by PERMA No. 1 of 2016 concerning Mediation Procedures in Court and Regulation of the Head of the National Land Agency Number 3 of 2011 concerning Management of Assessment and Handling of Land Cases which has been replaced by Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 11 of 2016 concerning Case Settlement Land. Mediation is carried out according to the agreement between both parties using the help of a mediator as an intermediary.